Pulpotomy medicaments in primary teeth: A literature review of natural alternatives - Kanamarlapudi Venkata Saikiran; Rekhalakshmi Kamatham; Putta Sai Sahiti; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2018)
Pulpotomy is a procedure which involves complete amputation of the coronal pulp, followed by employment of an appropriate medicament that will stimulate healing and preserve the vitality of the tooth. This is the choice of treatment for cariously exposed vital primary molars, with formocresol considered as golden standard. However, controversies surrounding this medicament have generated inquisitiveness to exploration for natural alternatives. This narrative review is to focus on the use of natural products as alternative pulpotomy agents to formocresol so as to guide the clinicians in choosing proper medicament.